2016
DOI: 10.1371/journal.pone.0166277
|View full text |Cite
|
Sign up to set email alerts
|

Disease Type- and Status-Specific Alteration of CSF Metabolome Coordinated with Clinical Parameters in Inflammatory Demyelinating Diseases of CNS

Abstract: Central nervous system (CNS) inflammatory demyelinating diseases (IDDs) are a group of disorders with different aetiologies, characterized by inflammatory lesions. These disorders include multiple sclerosis (MS), neuromyelitis optica spectrum disorder (NMOSD), and idiopathic transverse myelitis (ITM). Differential diagnosis of the CNS IDDs still remains challenging due to frequent overlap of clinical and radiological manifestation, leading to increased demands for new biomarker discovery. Since cerebrospinal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 53 publications
(54 reference statements)
0
31
2
Order By: Relevance
“…There have been reports about the correlation of increased lactate levels and development of various diseases including cancer and rheumatoid arthritis synovitis (9,14). Recent reports have demonstrated that the lactate levels in CSF from clinical patients with NMOSD were elevated (6,7). We hypothesized that the suppression of LDHA would downregulate LPS-induced inflammatory response in RAW 264.7 macrophages.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…There have been reports about the correlation of increased lactate levels and development of various diseases including cancer and rheumatoid arthritis synovitis (9,14). Recent reports have demonstrated that the lactate levels in CSF from clinical patients with NMOSD were elevated (6,7). We hypothesized that the suppression of LDHA would downregulate LPS-induced inflammatory response in RAW 264.7 macrophages.…”
Section: Discussionmentioning
confidence: 92%
“…Inhibition of lactate dehydrogenase A suppresses expression of cytokines. Lactate is implicated in excessive cell proliferation and autoimmune diseases (6,11). Therefore, we hypothesized that modulation of lactate regulates inflammatory response induced by LPS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gas chromatography coupled with mass spectrometry (GC-MS) has been recognized as a primary tool for small molecule analysis, 39 and is still used to detect various metabolic disorders today. 40 Recent interest in metabolomics stems from the ability to carry out more comprehensive metabolome analysis using new liquid chromatography combined with mass spectrometry (LC-MS), which has the potential to discover and identify both disease and pharmaceutical biomarkers, exploring the hidden secrets of the biochemical processes of tissues and cells. 41,42 Advances in LC-MS are very impressive, with recent developments in UPLC, the speed of analysis is further improved.…”
Section: Chromatography-mass Spectrometrymentioning
confidence: 99%